Extensor mechanism reconstruction in low-grade fibromyxoid sarcoma around the knee: case report - Mena Parco, Raul (2023)
Introduction: Low-grade fibromyxoid sarcoma is a malignant tumor with a high risk of developing recurrence and metastasis, surgical resection with wide margins is the main treatment, limb preservation and reconstruction is in high demand for surgeons. Case of report: We present the case of a 67-year-old woman with a recurrence of a knee tumor that had been operated on two year earlier. Oncological resection of the tumor was performed with reconstruction of the knee joint with an Endo Model prosthesis and extensor mechanism reconstruction with a synthetic polypropylene mesh graft plus a semitendinosus and gracilis autograft. The patella was reconstructed with posterior femoral condyle autograft. At 16 months of patient follow-up, she is free of disease, with a score of 27 on the lower limb scale of the MSTS (Musculoskeletal Tumor Society). Conclusion: The combination of synthetic graft with hamstring autograft can reduce the failure rate of extensor mechanism reconstruction due to oncological resections.